Study on the Identification of Cricket Cultivation Process as an Alternative for Economic Empowerment - Perwitasari, Alfita; Priansyah, Zildjianita; Zahra, Jihan Khairunnisa; Edgina, Ivahzada Marella; Kausar, Muhammad; Wihasnanto, Herry (Santoso Academy Network, 2025)
Community service activities in Babakanraden Village located in Cariu District, Bogor Regency, where nearly half of the population works as farmers and some residents cultivate crickets aim to strengthen local knowledge and skills related to cricket cultivation. Interviews revealed several key findings: male and female crickets can be distinguished by the number of tails; effective cricket habitats must use materials that are durable and resistant to being bitten; and crickets can be processed not only into flour but also into side dishes and community snacks. This activity has generated positive and empowering impacts for the village community. First, enhanced understanding of proper cultivation techniques equips residents with practical skills to improve productivity and quality. Second, recognizing crickets’ potential as diversified food products creates opportunities for added-value processing, supporting micro-entrepreneurship and increasing household income potential. Overall, the program not only provides knowledge but also strengthens community empowerment through improved technical capacity and expanded economic opportunities.